2003
DOI: 10.1007/s00467-003-1280-4
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in uremia assessed by heart rate variability

Abstract: Decreased heart rate variability is an independent risk factor for cardiac mortality in hemodialysis patients. Our aim was to determine whether it is already present in uremic children and young adults on hemodialysis and following renal transplantation. Twenty-two hemodialysis patients [age 17.2 years (median, quartiles 13.0-22.6)], 22 transplant patients [18.4 years (14.4-21.2)], and 29 healthy controls [16.4 years (15.7-21.1)] were examined. Heart rate and its high (HF) and low (LF) frequency variability we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…34 A reduction of HRV in ESRD patients has been demonstrated in some earlier reports, [19][20][21]35 whereas some other groups reported increased LF power. 36 This discrepancy may be related to clinical or methodological differences.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…34 A reduction of HRV in ESRD patients has been demonstrated in some earlier reports, [19][20][21]35 whereas some other groups reported increased LF power. 36 This discrepancy may be related to clinical or methodological differences.…”
Section: Discussionmentioning
confidence: 82%
“…The reasons for these changes are unexplained but may be suspected due to the fact that the HD patients nearly have abnormal autonomic function. [19][20][21]34 Also, another reason is that autonomic function fluctuates depending on sleep dynamics when non-REM sleep is accompanied by an augmentation of parasympathetic tone with depression of sympathetic activity, and REM sleep shows reverse change. 26,27 The autonomic function is even synchronized with REM/non-REM ultradian sleep rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,12,17,18 The HRV reduction in patients with CKD is considered a risk factor for the occurrence of cardiac arrhythmias, and is associated with a higher cardiovascular mortality. 4,5 Cashion et al 19 , assessing hemodialysis patients by use of 24-hour Holter to study HRV in the time and frequency domains for a period of two years, have reported that the reduction in the SDNN, LF, and LF/HF parameters predicted cardiovascular death, especially sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…In that population, the reduction in HRV associated with injury to the parasympathetic system due to the structural impairment of arteries or the functional alterations of the autonomic nervous system secondary to uremic toxins. [18][19][20] The increase in HRV in patients with CKD has been observed with kidney transplantation and the practice of exercise programs. 10,11,21,22 The present study did not show an increase in the HRV assessed in the time and frequency domains after 12 weeks of aerobic training.…”
Section: Discussionmentioning
confidence: 99%